Nehru Yuva Kendra Scheme - A Quick Study 1990-91 - Planning Commission (Planning Commission Government of India, 1990)
The Nehru Yuva Kendra Scheme (NYKS), established in 1972, aims to engage non-student rural youth aged 15–35 in national development and personal skill enhancement through a network of youth clubs and voluntary organizations. An evaluation conducted in 1990 by the Planning Commission assessed the scheme’s outreach, administrative efficiency, financial management, and socio-community impact. Findings indicate that while NYKS successfully raised awareness among rural youth on development and environmental issues, participation was limited, particularly among females (2.4%) and marginalized communities. Administrative challenges included staffing insecurity and insufficient coordination with other development departments, while financial management was efficient but primarily allocated to salaries and direct program costs. NYKS activities, including vocational training, functional literacy, and rural sports, positively influenced local governance and youth mobilization. Recommendations highlight the need for sustained funding mechanisms, strengthened inter-departmental linkages, and enhanced personnel training to improve operational effectiveness. Overall, the NYKS demonstrates significant potential in mobilizing rural youth for community development, contingent on continuous structural and strategic improvements to meet evolving rural and developmental demands.
Programme Evaluation Organisation Planning Commission Government of India New Delhi-1 March, 1991
Keywords: Nehru Yuva Kendra Scheme; Rural Youth; Skill Development; Youth Clubs; Community Engagement; Administrative Support; Financial Management; Vocational Training; Panchayat Collaboration; Gender Disparity; Capacity Building; Rural Development